The Effect of Conductivity on Surface Leakage Currents on Iced-Covered Insulators - Özküçük, Muhammed Buğracan; Gençoğlu, Muhsin Tunay (My University, 2023)
Insulators on power transmission systems today are vital to ensuring high-voltage lines' reliable and effective operation. However, insulators will inevitably encounter problems such as contamination and icing due to natural environmental conditions and environmental factors. Pollution layers and ice buildup that have developed on insulator surfaces harm insulation performance, increase surface leakage currents, and result in power line failures or interruptions. This article focuses on understanding the phenomena of contamination and icing in insulators, evaluating their effects, and investigating methods that can be taken to prevent or reduce these problems. For this purpose, solutions with different conductivity values (1000–4000 ?S/cm) were sprayed on the insulators in the laboratory environment, and ice covering the insulator surface was provided. An alternating voltage (5–20 kV) with the frequency of the mains was applied to the insulators to study leakage currents. Data were obtained with the help of the LabVIEW program, and the relationship between leakage currents of porcelain, glass, and silicone insulators and conductivity was compared. The amplitude of leakage current increases with the increase in conductivity in all three types of insulators. The increase in leakage current with conductivity is most observed in the glass insulator, while the least affected element is the silicon insulator.
Keywords: LabVIEW; Ice-covered insulator; Surface conductivity; Leakage current; AC voltage